Comparative Statement Analysis of Select Defence Sector Companies in India - Kumar, Amrendra (Journal of Economics and Management, 2025)
The Indian defence sector has emerged as a critical pillar of national security, economic self-reliance, and industrial innovation. Within this ecosystem, Hindustan Aeronautics Limited (HAL) and Bharat Electronics Limited (BEL) occupy central positions as leading public sector undertakings (PSUs) under the Ministry of Defence. This research paper undertakes a comprehensive comparative statement analysis of HAL and BEL of FY 2024–2025, with the objective of evaluating their financial performance, operational efficiency, and governance practices. Using a mixed-methods ex-post-facto research design, the study integrates quantitative tools such as ratio analysis, DuPont decomposition, common-size analysis, and event studies, alongside qualitative content analysis of auditor reports, management discussions, and governance disclosures. The findings reveal distinctive patterns in profitability, liquidity, solvency, and efficiency across the two entities, reflecting both firm-specific strategies and sectoral dynamics influenced by defence policy, budgetary allocations, and global geopolitical developments. While HAL demonstrates resilience in order execution and R&D intensity, BEL exhibits stronger working capital management and a more consistent dividend policy. The study also highlights governance challenges, notably the lack of independent directors and recurring audit remarks, which have implications for transparency and long-term sustainability. This paper contributes to the literature on financial statement analysis by situating defence PSUs within the broader discourse of corporate governance, financial accountability, and industrial policy. The analysis is intended to serve as a reference for researchers, college students, and educationists exploring the intersection of accounting, finance, and public-sector performance.